Aseptic Raman spectroscopy can detect changes associated with the culture of human dental pulp stromal cells in osteoinductive culture. Issue 21 (16th September 2015) - Mitchell, Adam; Ashton, Lorna; Yang, Xuebin B.; Goodacre, Royston; Tomlinson, Matthew J.; Smith, Alistair; Kirkham, Jennifer
Abstract : There is an unmet need for the non-invasive characterisation of stem cells to facilitate the translation of cell-based therapies. Abstract : There is an unmet need for the non-invasive characterisation of stem cells to facilitate the translation of cell-based therapies. Raman spectroscopy has proven utility in stem cell characterisation but as yet no method has been reported capable of taking repeated Raman measurements of living cells aseptically over time. The aim of this study was to determine if Raman spectroscopy could be used to monitor changes in a well characterised cell population (human dental pulp stromal cells (DPSCs)) by taking repeated Raman measurements from the same cell populations in osteoinductive culture over time and under aseptic conditions. DPSCs were isolated from extracted premolar teeth from 3 consenting donors. Following in vitro expansion, DPSCs were maintained for 28 days in osteo-inductive medium. Raman spectra were acquired from the cells at days 0, 3, 7, 10, 14 and 28. Principal component analysis (PCA) was carried out to assess if there was any temporal spectral variation. At day 28, osteoinduction was confirmed using alizarin red staining and qRT-PCR for alkaline phosphatase and osteocalcin. Alizarin red staining was positive in all samples at day 28 and significant increases in alkaline phosphatase ( p < 0.001) and osteocalcin ( p < 0.05) gene expression were also observed compared with day 0. PCA of the Raman data demonstrated trends in PC1 from days 0–10, influenced by protein associated features and PC2 from days 10–28, influenced by DNA/RNA associated features. We conclude that spectroscopy can be used to monitor changes in Raman signature with time associated with the osteoinduction of DPSCs using repeated measurements via an aseptic methodology.